Prognostic value of tumour-associated neutrophils in different polarization status releasing neutrophil extracellular traps in the immunotherapy of advanced non-small cell lung cancer - Hong, Weiwei; Ye, Xin; Chen, Lin; Chai, Xiangzhi; Yin, Yan; Li, Zhaoqing; Fang, Chen; Qian, Xiaoying; Yu, Biao; Qin, Guizhen; Yao, Xinyuan; Zhou, Bingbiao; et al. (Frontiers in Oncology, 2026)
PurposeThis study analyzed the polarization types of tumour-associated neutrophils (TANs) that release neutrophil extracellular traps (NETs), as well as the impact of neutrophil polarization on the efficacy of immunotherapy for non-small cell lung cancer (NSCLC).MethodsThis study retrospectively collected clinical data and pathological samples of 115 patients with advanced NSCLC who underwent first-line immunotherapy. Multiplex immunofluorescence staining was used to assess TANs polarization status and NETs expression.ResultsWe found that the presence of NETs was negatively associated with tumour-associated N1 neutrophil (P < 0.001) but positively associated with tumour-associated N2 neutrophil (P < 0.001). Further analysis revealed that the NETs-low group experienced prolonged progression-free survival (PFS) (15.0 vs 9.9 months, P = 0.045) and overall survival (OS) (40.5 vs 22.0 months, P = 0.002) with first-line immunotherapy compared with the NETs-high group. We also found that there was no significant difference in the efficacy of immunotherapy between those with tumour-associated N1 neutrophils exhibiting low NETs and those exhibiting high NETs. However, patients with tumour-associated N2 neutrophils exhibiting low NETs expression experienced improved PFS (17.3 vs 9.2 months, P = 0.008) and OS (40.5 vs 18.3 months, P < 0.001) compared with that exhibiting high NETs expression. We also found that tumour-associated N2 neutrophil expressing NETs was negatively associated with CD8+ T cell infiltration, but positively associated with Treg cell infiltration.ConclusionTumour-associated N2 neutrophils in NSCLC tissues are the primary cells releasing NETs, and tumour-associated N2 neutrophils with high NETs expression are associated with an immunosuppressive tumour microenvironment, which will impact the efficacy of first-line immunotherapy in NSCLC patients.